Penyuluhan Strategi Berinovasi Melalui Design Thinking dengan Konsep Efektuasi untuk Kesiapan Siswa dalam Berwirausaha di SMA Muhammadiyah Cerme 8 Gresik - Sukaris Sukaris; Alkusani Alkusani; Heru Baskoro (Jurnal Pengabdian Manajemen, 2023)
The problem that occurs when prospective high school graduates feel hesitant to choose to become an entrepreneur is they do not have capital, do not have a unique business idea, are not ready for the risks, do not have family support, are unsure of their own abilities, do not know where to start, and want to seek experience. formerly. However, activities to foster interest in entrepreneurship continue to be pursued including double track program activities, which are expected to increase motivation, as well as SMA Muhammadiyah 8 Cerme needs to continue to carry out outreach, seminars, events, other festivals that lead to activities to increase entrepreneurial capacity so that they are increased quality and quantity. Therefore, training in entrepreneurship to innovate through design thinking is important in equipping prospective graduates to have the knowledge and preparation with the best assets they currently have. This activity is intended so that prospective graduates or high school students who have received this socialization will be able to have entrepreneurial skills that are useful when starting a business of their own. This activity was carried out offline at the SMA Muhammadiyah 8 Cerme Gresik location. The method used with socialization is in the form of in-class seminars. The results of the dedication show that the participants have shown a good understanding of the effectuation material presented and the participants are ready to implement it on their current assets, businesses and products.